Securing Property Rights for Women and Men in Rural Benin - Goldstein, Markus (World Bank, Washington, DC, 2016)
Women in Sub-Saharan Africa are less likely than men to own land. They also use less land and have lower tenure security over the land that they use. This gap is costly in terms of lost productive output. The early results showed that improved tenure security through land demarcation increased long-term investments in cash crops and trees and erased the gender gap in land fallowing - a key soil fertility investment. It is important that interventions cover as much of a household’s landholdings as possible: the authors found that some women shifted their agricultural production to plots of land that did not benefit from demarcation so that they can guard these less secure and less productive plots. The rural land use plans (plans fonciers ruraux (PFR)) in Benin represent a more decentralized, low-cost approach to land rights formalization. The PFR program is innovative in its focus on the formalization of existing customary rights of individual landholders. The objectives of the program are to improve tenure security and stimulate agricultural investment in rural areas. The World Bank’s Africa gender innovation lab, in collaboration with researchers from the development research group and the Paris school of economics, set out to evaluate the PFR program’s impact through a randomized controlled trial. This study provides the first set of experimental evidence on the causal impact of a large-scale land formalization program.